A Study on CO2 Methanation and Steam Methane Reforming over Commercial Ni/Calcium Aluminate Catalysts - Gabriella Garbarino; Federico Pugliese; Tullio Cavattoni; Guido Busca; Paola Costamagna (Energies, 2020)
Three Ni-based natural gas steam reforming catalysts, i.e., commercial JM25-4Q and JM57-4Q, and a laboratory-made catalyst (26% Ni on a 5% SiO2–95% Al2O3), are tested in a laboratory reactor, under carbon dioxide methanation and methane steam reforming operating conditions. The laboratory catalyst is more active in both CO2 methanation (equilibrium is reached at 623 K with 100% selectivity) and methane steam reforming (92% hydrogen yield at 890 K) than the two commercial catalysts, likely due to its higher nickel loading. In any case, commercial steam reforming catalysts also show interesting activity in CO2 methanation, reduced by K-doping. The interpretation of the experimental results is supported by a one-dimensional (1D) pseudo-homogeneous packed-bed reactor model, embedding the Xu and Froment local kinetics, with appropriate kinetic parameters for each catalyst. In particular, the H2O adsorption coefficient adopted for the commercial catalysts is about two orders of magnitude higher than for the laboratory-made catalyst, and this is in line with the expectations, considering that the commercial catalysts have Ca and K added, which may promote water adsorption.